Behçet's Syndrome in a Chinese Pedigree of NLRP3-Associated Autoinflammatory Disease: A Coexistence or Novel Presentation? - Liu, Jinjing; Yu, Xin; Li, Chaoran; Wang, Yi; Yu, Weihong; Shen, Min; Zheng, Wenjie (Frontiers in Medicine, 2021)
Objectives:NLRP3-associated autoinflammatory disease (NLRP3-AID) and Behçet's syndrome (BS) both belong to autoinflammatory diseases and rarely co-occur. Here we reported a Chinese pedigree of NLRP3-AID presented with BS. Methods: We recorded a Chinese pedigree of NLRP3-AID presented with BS. Whole-exome sequencing was performed to find the hereditary susceptibility gene, and Sanger sequencing was performed on a consecutive cohort of 30 BS patients. We also reviewed the English literature on vasculitis associated with NLRP3-AID. Results: The proband was a 45-year-old Chinese Han woman. She and her 12-year-old daughter presented with recurrent fevers, cold-induced urticaria, oral, and genital ulcers, conjunctivitis, uveitis, optic atrophy, erythema nodosum, headache, and hearing loss. They were initially suspected of having BS, and both responded poorly to corticosteroids and immunosuppressants, while anti-TNF therapy was moderately effective. Pedigree analysis revealed another four relatives with similar symptoms, and a heterozygous NLRP3 gene mutation c.1316C>T, p.Ala439Val was identified by whole-exome sequencing and Sanger sequencing. However, we did not discover NLRP3 gene mutation by Sanger sequencing in a confirmative cohort of 30 BS cases. A few case reports of vasculitis coexisting with NLRP3-AID, including a case of glomerulonephritis, and five cases of retinal vasculitis, were summarized through literature review. Conclusions: Our study is the first report of NLRP3-AID associated with BS. The coexistence of NLRP3-AID and BS reveals the extensive heterogeneity of the pathogenesis of systemic autoinflammatory diseases and calls for specific therapeutics.